Efficiency enhancement of the reltron oscillator using four-grid asymmetrical RF interaction cavity. Issue 14 (22nd September 2022) - Tripathi, Prabhakar; Kumar, Arjun; Dwivedi, Smrity; Jain, P. K.
Abstract : In this article, a modified reltron was proposed. Here an asymmetrical radio frequency (RF) modulation cavity interaction structure was used which consists of three coupled cavities instead of two used in the conventional reltron. Hence, instead of three grids in its modulation cavity, the proposed modified reltron structure consists of four grids. This additional grid inside the modulation cavity: distributes the length of the modulation cavity asymmetrically, which helps to form tight and dense electron bunches within the device. The proposed structure was designed and simulated using a CST Studio Suite. For the optimized grid spacing, the results of the PIC simulation showed the modified reltron was able to produce ∼350 MW power at 2.75 GHz frequency which was ∼100 MW more than the reltron. With the typically selected device's electric parameters the device efficiency was also found ∼41.2 % which was ∼11 % higher than previously reported results.